Adult report of childhood exposure to parental alienation at different developmental time periods. Issue 4 (10th October 2017) - Verrocchio, Maria Christina; Baker, Amy J. L.; Marchetti, Daniela
Abstract: The purpose of this study was to determine the relationship between exposure to Parental Alienation (PA) at different developmental time periods and psychological maltreatment. Three hundred and sixty‐one adults in Chieti, Italy completed an anonymous and confidential paper and pencil survey regarding their childhood exposure to twenty PA behaviours across three developmental time periods as well as a measure of psychological maltreatment by each parent. Results revealed that exposure to PA at each time period was significantly associated with psychological maltreatment. Moreover, the number of time periods of exposure to PA (from 0 to 3) was associated with psychological maltreatment. This was true for PA by mothers and PA by fathers. Implications for policy and practice are discussed. Practitioner points: Mental health professionals can use the results of this study to guide their intervention efforts Co‐parenting educators can incorporate these results into their routine efforts to help parents be aware of PA and its effects Targeted parents can use these findings to make the case for timely legal and mental health interventions